ORGANIZATIONAL MODELS OF “ONE-STOP” CLINICS FOR THYROID DISEASE: A REVIEW OF PROCESSES, PERFORMANCE INDICATORS, AND OUTCOMES FROM THE LITERATURE - Milić, Marko Kimi; Sinanović, Šćepan; Kostić, Dejan; Ratković, Milena (Medical Gazzette, 2026)
Background: Fragmented care pathways for thyroid nodular disease prolong time to decision and increase costs. “One-stop” clinics (OSCs) integrate clinical evaluation, ultrasound, ultrasound-guided fine-needle aspiration (FNA) and, when appropriate, rapid on-site evaluation (ROSE)/telecytology in a single visit.Objective: To map organizational models of OSCs, define key performance indicators (KPIs), and summarize outcomes (time, visits, adequacy, repeat FNA, costs, patient satisfaction, safety).Methods: Scoping review following PRISMA-ScR and JBI guidance. MEDLINE, Scopus, and Web of Science were searched (2000–August 2025). We included studies that operationalized OSCs and/or reported KPIs/outcomes. Data extraction covered organizational features, protocols (ACR/EU-TIRADS, Bethesda), flow metrics, FNA/ROSE adequacy, economics, satisfaction, and safety. Narrative synthesis was performed.Results: Identified OSC models consistently shorten lead time to decision and reduce the number of visits. Sample adequacy is high—especially with ROSE/telecytology—thereby lowering repeat FNA rates. Patient satisfaction is high; the safety profile of FNA remains favourable. Economic analyses indicate that the cost-effectiveness of ROSE is context-dependent and greatest when baseline inadequacy is higher and/or ROSE costs are lower. A KPI set is proposed: lead time, proportion of “single-visit” completions, Bethesda I rate, ROSE utilization, repeat FNA ≤90 days, cost per episode, and satisfaction.Conclusion: OSCs are an applicable, value-oriented model for thyroid diagnostics. Selective use of ROSE/telecytology and KPI-driven management enable efficient and safe implementation across diverse resource settings.
Keywords: one-stop clinic; thyroid; ultrasound; fine-needle aspiration; ROSE; TIRADS; Bethesda; performance indicators; health management